NADPH‐dependent 5‐keto‐D‐gluconate reductase is a part of the fungal pathway for D‐glucuronate catabolism. Issue 1 (30th December 2017) - Kuivanen, Joosu; Richard, Peter
Abstract : NADPH‐dependent 5‐keto‐D‐gluconate reductase was identified as a missing element in the pathway for D‐glucuronate catabolism in fungi. The disruption of the gene, gluF, by CRISPR/Cas9 in the filamentous fungus Aspergillus niger resulted in a strain unable to catabolise D‐glucuronate. The purified GluF protein was characterized and k cat and K m values of 23.7 ± 1.8 s −1 and 3.2 ± 0.1 mm for 5‐keto‐D‐gluconate, respectively, were determined. The enzyme is reversible and is active with NADP + and D‐gluconate. We suggest a pathway for D‐glucuronate catabolism with the intermediates L‐gulonate, 2‐keto‐L‐gulonate, L‐idonate, 5‐keto‐D‐gluconate, D‐gluconate and D‐gluconate‐6‐phosphate which is a part of the pentose phosphate pathway. A fungal enzyme activity for the conversion of L‐gulonate to 2‐keto‐L‐gulonate remains to be identified. Abstract :